Pengaruh Risiko Kredit dan Bank Size Terhadap Profitabilitas Bank Umum Syariah milik BUMN di Indonesia Sebelum Merger - Muttaqin, Ibnu; Qomar, Moh. Nurul (Jurnal BAABU AL-ILMI: Ekonomi dan Perbankan Syariah, 2022)
The objective of the research is to discuss the relationship between the internal factors of bank profitability of Islamic commercial banks belonging to State-Owned Enterprises (BUMN) in Indonesia before the merger. The independent variables are credit risk which is represented by non-performing loan and loan loss provision and bank size, with the dependent variable is bank profitability using two proxies return on asset and return on equity. This study uses secondary data from quarterly reports with population data before 2020 (before the merger). The sample used the purposive sampling method from 2016 to 2020, to obtain 60 data. This study uses panel data analysis. The results show that NPL has a significant negative effect on profitability both ROA and ROE, while LLP has no effect on profitability both ROA and ROE, bank size has a significant negative effect on ROA but has no effect on ROE